Pengaruh Kualitas Pelayanan Posyandu Terhadap Partisipasi Ibu dalam Pencegahan Stunting: Studi di Wilayah Rural Kabupaten Lima Puluh Kota - Cahyani, Fauziah; Saputra, Boni (Jurnal Ilmu Administrasi Negara AsIAN (Asosiasi Ilmuwan Administrasi Negara), 2025)
Stunting has emerged as a critical public health challenge threatening human resource quality in Indonesia, with a national prevalence of 21.5% exceeding the WHO tolerance threshold of 20%. Situjuah Limo Nagari Sub-district faces substantial challenges with 110 reported stunting cases and fluctuating maternal participation rates in posyandu programs ranging from 36-60%, indicating a misalignment between service quality and community engagement. This study aims to analyze the influence of posyandu service quality on maternal participation in stunting prevention programs in Situjuah Limo Nagari Sub-district, Lima Puluh Kota Regency. The research employed a quantitative associative approach utilizing simple random sampling of 87 mothers with stunted children, implementing validated instruments measuring five SERVQUAL service quality dimensions and three participation indicators. The analysis revealed a significant influence of service quality on maternal participation with a coefficient of determination R² = 0.580 (58%) and t-calculated = 10.002 > t-table = 1.988 at significance level p < 0.001. The regression equation Y = 10.871 + 0.354X confirms that each unit increase in service quality enhances participation by 0.354 units. These findings provide empirical justification for investing in posyandu service quality improvement as a cost-effective strategy for optimizing community participation and achieving sustainable stunting reduction targets.